Optimization of the Process for Defatting Sea Cucumber Powder by Supercritical CO2 Extraction and Its Effect on Volatile Flavor Compounds - Gongming WANG; Hui HUANG; Yuzhu DING; Jinglin XUE; Zhiqiang SHU; Yuexin JING; Chunna JIAO; Jian ZHANG (Shipin gongye ke-ji)
In this study, supercritical CO2 extraction conditions for sea cucumber powder were optimized using single factor and orthogonal experimental design, with defatting rate as an indicator. The fatty acid composition of the sea cucumber powder before and after extraction as well as that in the supercritical CO2 extract were detected using gas chromatography, and supercritical CO2 extraction of volatile flavor substances was investigated using headspace-gas chromatography-ion migration spectroscopy (HS-GC-IMS). The results showed that the optimal conditions for supercritical CO2 extraction was optimized using single factor and orthogonal experiment, with an extraction temperature of 60 ℃, extraction pressure of 40 MPa, extraction time of 2 h, and a degreasing rate of 57.6%±3.89%. A total of 25 fatty acids were detected in the sea cucumber powder, extracted sea cucumber powder, and supercritical CO2 extract, with a higher proportion of monounsaturated fatty acids in the supercritical CO2 extract. In contrast, the proportions of polyunsaturated fatty acids such as arachidonic acid (ARA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) were higher in the extracted sea cucumber powder. HS-GC-IMS led to the identification of 70 volatile components. Notably, substances with fishy or pungent odors such as dimethyl sulfide, butanal, E-2-butenal, pentanal, heptanal, benzaldehyde, pentanol, 2-butanone, 2-hexanone, 3-hexanone and other substances were significantly reduced in the extracted sea cucumber powder, substantially improving the overall flavor. Therefore, supercritical CO2 extraction can effectively separate lipids from sea cucumber powder, while removing a large amount of volatile components with fishy odors.